The Pope of Physics - Yock, Philip (New Zealand Science Review, 2017)
​Enrico Fermi was one of the towering figures of twentieth century physics and often considered the last person to have known all of physics. Not for him the title ‘theoretical physicist’, or ‘experimentalist’– his realm was physics wherever that might take him. He made seminal contributions to quantum field theory, beta-type radioactivity, nuclear interactions induced by neutrons, nuclear fission and the origin of cosmic rays. He earned the title ‘Pope of Physics’ in his home country of Italy because his judgements on physics turned out to be, with one possible exception, unfailingly correct. He is remembered as Italy’s most famous scientist since Galileo.